Perancangan Ulang Interior Rumah Sakit Umum Daerah Singaparna Medika Citrautama (smc) Kabupaten Tasikmalaya Dengan Pendekatan Indoor Health And Comfort (ihc) - Ivana Putri, Amanda; Faza Surya Rusyda, Hana; Sri Ismiranti, Athifa (eProceedings of Art & Design, 2024)
Singaparna Medika Citrautama (SMC) Regional General Hospital is located at Jl. Raya Rancamaya, Tasikmalaya Regency, West Java. This research aims to redesign the interior of the Singaparna Medika Citrautama Regional General Hospital (SMC) of Tasikmalaya Regency with the Indoor Health and Comfort (IHC) approach. The IHC approach emphasizes the importance of creating a healthy and comfortable indoor environment that improves the well-being of patients and health workers. In the research design the methods used include observation, interviews with medical staff, and surveys to patients and visitors to understand their needs and expectations of the hospital interior space. The findings from this study suggest that interior redesign should prioritize the use of natural light, ventilation, and materials that promote a sense of calm and relaxation. In addition, components that encourage social interaction and community building among patients and healthcare workers should be included in the design. This study found that the Indoor Health and Comfort (IHC) method can significantly improve the hospital environment, which impacts on better patient outcomes and satisfaction levels in both employees and doctors. The findings of this study can serve as a reference for future hospital design projects, emphasizing the importance of integrating indoor health and comfort principles into the design process. Keywords: redesign, interior, regional general hospital, Indoor Health and Comfort (IHC)